2012
DOI: 10.1152/ajpgi.00402.2011
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA polymerase editing mutation, PolgD257A, disturbs stem-progenitor cell cycling in the small intestine and restricts excess fat absorption

Abstract: Changes in intestinal absorption of nutrients are important aspects of the aging process. To address this issue, we investigated the impact of accelerated mitochondrial DNA mutations on the stem/progenitor cells in the crypts of Lieberkühn in mice homozygous for a mitochondrial DNA polymerase gamma mutation, Polg D257A, that exhibit accelerated aging phenotype. As early as 3–7 mo of age, the small intestine was significantly enlarged in the PolgD257A mice. The crypts of the PolgD257A mice contained 20% more ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 53 publications
(67 reference statements)
3
45
0
Order By: Relevance
“…Precedent for such a relationship was described in humans where mitochondrial DNA mutations resulting in respiratory chain defects were associated with reduced proliferation and increased apoptosis of colonic crypt cells taken from elderly subjects, who frequently present with intestinal malabsorption (36,44). Mutation of the proofreading function of the mitochondrial DNA polymerase gamma in mice, which results in progressive mitochondrial DNA mutation and dysfunction, is also associated with reduced dietary fat absorption (13,28,45). Although there is strong evidence of reduced mitochondrial respiratory chain protein abundance and function in the ventral midbrain of Park2 KO mice, as well as susceptibility to mitochondrial dysfunction in cardiac myocytes (37,39), no such evidence exists for Park2 KO intestinal epithelial cells, and this merits further study.…”
Section: Discussionmentioning
confidence: 99%
“…Precedent for such a relationship was described in humans where mitochondrial DNA mutations resulting in respiratory chain defects were associated with reduced proliferation and increased apoptosis of colonic crypt cells taken from elderly subjects, who frequently present with intestinal malabsorption (36,44). Mutation of the proofreading function of the mitochondrial DNA polymerase gamma in mice, which results in progressive mitochondrial DNA mutation and dysfunction, is also associated with reduced dietary fat absorption (13,28,45). Although there is strong evidence of reduced mitochondrial respiratory chain protein abundance and function in the ventral midbrain of Park2 KO mice, as well as susceptibility to mitochondrial dysfunction in cardiac myocytes (37,39), no such evidence exists for Park2 KO intestinal epithelial cells, and this merits further study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hematopoietic progenitor cells of the mtDNA mutator mice are affected during fetal development, and their neural stem cells exhibit declining quiescence and decreased self-renewal capacity in response to mtDNA mutation accumulation 98 . Another study reported decreased proliferation and increased apoptosis of epithelial crypt cells in mtDNA mutator mice and impaired in vitro development of stem cell–derived organoids 99 . The abnormal phenotypes observed in somatic stem cells from mtDNA mutator mice can be rescued by supplementation with NAC, implying that mtDNA mutations alter the oxidative state of stem cells and that this impairs their functional capacity 98 .…”
Section: Mitochondrial Dysfunction and Stem Cell Agingmentioning
confidence: 99%
“…The lack of proofreading activity of the so-called “Mutator mice” caused the accumulation of mtDNA point mutations and non-canonical multiple deletions in different tissues, leading to a progressive OXPHOS deficiency (Edgar, 2009; Trifunovic, 2004). Despite the different age of onset, these mice showed a reduced lifespan and developed a premature aging phenotype (Fox, 2012; Kujoth, 2005; Trifunovic, 2004). Unexpectedly, the accumulation of mtDNA mutations did not induce a massive chronic oxidative stress and the progeroid phenotype was mainly caused by increased apoptosis (Kujoth, 2005; Trifunovic, 2005).…”
Section: Mouse Models Of Proteins Involved In Mtdna Stability Repmentioning
confidence: 99%
“…Recent work demonstrated that the Mutator mouse also showed profound changes in intestinal absorption of nutrients even at 3 to 7 months of age, with restricted absorption of dietary lipids due to a severe impairment of stem/progenitor cells (Fox, 2012). …”
Section: Mouse Models Of Proteins Involved In Mtdna Stability Repmentioning
confidence: 99%